2007
DOI: 10.2106/jbjs.f.01037
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Lighting During Orthopaedic Surgery and the Rate of Infection

Abstract: When appropriate safety precautions are taken, ultraviolet lighting appears to be an effective way to lower the risk of infection in the operating room during total joint replacement surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 13 publications
1
36
0
Order By: Relevance
“…For example at a fluence of 207-nm light that produce four logs of MRSA cell kill, there is much less than one decade of cell kill in human cells (as discussed above, we chose four logs of bacterial kill for this comparison because studies of wound irradiation with conventional UV germicidal lamps suggest that this level of bacterial reduction will produce significant decreases in SSI rates [8]). In contrast with the results for 207-nm light, while conventional germicidal lamps efficiently kill MRSA, conventional germicidal lamps are almost as efficient at killing human cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example at a fluence of 207-nm light that produce four logs of MRSA cell kill, there is much less than one decade of cell kill in human cells (as discussed above, we chose four logs of bacterial kill for this comparison because studies of wound irradiation with conventional UV germicidal lamps suggest that this level of bacterial reduction will produce significant decreases in SSI rates [8]). In contrast with the results for 207-nm light, while conventional germicidal lamps efficiently kill MRSA, conventional germicidal lamps are almost as efficient at killing human cells.…”
Section: Discussionmentioning
confidence: 99%
“…One approach which in principle overcomes the problem of drug resistance is the use of germicidal UV lamps [8], [9], because UV light is generally equi-effective at inactivating drug-resistant bacteria compared with wild-type strains [10], [11]. In fact studies of surgical wound irradiation with conventional germicidal UV lamps have shown great promise, with UV fluences corresponding to 4 to 5 logs of MRSA cell kill resulting in significant decreases in SSI rates [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of ultraviolet lighting was found to be correlated with reduced rates of PJI, however, the exposure hazards were 6 to 28 times greater than the recommended limits which also effects the orthopedic operating room personnel [92, 93]. Because of these safety concerns, there are recommendations against the routine use of UV lights in the OR [94-96].…”
Section: The Operation Daymentioning
confidence: 99%